1997
DOI: 10.1128/jb.179.20.6335-6340.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, nucleotide sequence, and overexpression of smoS, a component of a novel operon encoding an ABC transporter and polyol dehydrogenases of Rhodobacter sphaeroides Si4

Abstract: The gene coding for sorbitol dehydrogenase (SDH) of Rhodobacter sphaeroides Si4 was located 55 nucleotides upstream of the mannitol dehydrogenase gene (mtlK) within a previously unrecognized polyol operon. This operon probably consists of all the proteins necessary for transport and metabolization of various polyols. The gene encoding SDH (smoS) was cloned and sequenced. Analysis of the deduced amino acid sequence revealed homology to enzymes of the short-chain dehydrogenase/reductase protein family. For struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…1B), separated merely by polS (encoding sorbitol dehydrogenase), as in R. sphaeroides Si4 (57). Thus, the ABC transporter might also be active with other polyols, e.g., sorbitol.…”
Section: Resultsmentioning
confidence: 99%
“…1B), separated merely by polS (encoding sorbitol dehydrogenase), as in R. sphaeroides Si4 (57). Thus, the ABC transporter might also be active with other polyols, e.g., sorbitol.…”
Section: Resultsmentioning
confidence: 99%
“…ABC-T SMc01496 (CUT1) was induced by the C6 polyols dulcitol, sorbitol, mannitol, and maltitol (Glu␣1-4sorbitol) but not by sugars. It has high identity to the Smo system of Rhodobacter sphaeroides (28), with genes encoding a putative sorbitol dehydrogenase (smoS; SMc01500) and mannitol dehydrogenase (mtlK; SMc01501) downstream of SMc01496.…”
Section: Site the Results Are Shown In Full Inmentioning
confidence: 99%
“…While mannitol is a very good carbon source for S. coelicolor, growth on sorbitol is barely detectable. A gene cluster on cosmid SCI7 was found that could encode a permease (50). SmoD exhibits 30% identity to GutB, a sorbitol dehydrogenase present in Bacillus subtilis (27).…”
Section: Resultsmentioning
confidence: 99%